Model order reduction technique applied on harmonic analysis of a submerged vibrating blade - Tengs, Eric; Charrassier, Flora; Holst, Martin; Storli, Pal-Tore Selbo (Zielona Góra: Uniwersytet Zielonogórski)
As part of an ongoing study into hydropower runner failure, a submerged, vibrating blade is investigated both experimentally and numerically. The numerical simulations performed are fully coupled acoustic-structural simulations in ANSYS Mechanical. In order to speed up the simulations, a model order reduction technique based on Krylov subspaces is implemented.
Keywords: model order reduction; FSI; vibrations; harmonic response